Mammalia, Chiroptera, Phyllostomidae, Mimon crenulatum (Geoffroy St.-Hilaire, 1803): first Record for the Cerrado Biome in the State of Mato Grosso, Brazil - Sérgio Oliveira; Joaquim Silva; Ricardo Sousa; Karina Faria (Check List, 2013)
Two male individuals of Mimon crenulatum were captured in the Mario Viana Municipal Park, at Nova Xavantina, eastern Mato Grosso, Brazil. This record expands the species’ distribution in West-Central Brazil, and represents the first record for the Cerrado of Mato Grosso. The specimens’ morphometric data are presented and compared with those of specimens found in other biomes. Two predictive geographic distribution models were generated, indicating the expansion of the potential distribution of the species.